Redefining the refugee crisis: Examining the status of climate-induced refugees and internally displaced persons with special reference to India - A K, Nirupama; Mammen, Jeffin Thomas (Christ University Law Journal, 2024)
Climate change is causing drastic impacts across the world. Temperature change, rising sea levels, and frequent disasters like floods are increasing. People are forced to flee their homeland since their place becomes inhabitable, leaving them homeless as refugees. But policies have yet to be created specifically to deal with climate refugees. Although terminologies like "climate refugee" and "environmental refugee" have been used interchangeably, this research uses the term "climate refugee" to call attention to the social, economic, and political variables and how displaced people are moved and resettled. South Asian countries are highly prone to climate change impacts and produce climate refugees. In particular, this paper will examine India, where highly vulnerable populations are left homeless due to climate change impacts. This study is historical, descriptive and analytical in nature and has depended on primary sources like documents from the Government of India and secondary sources like books, journals for the purpose of analysis. The study concludes that the legal status of climate refugees is still a cliffhanger and recommends a more inclusive definition of refugees in international laws.